Business Development Through The Application Of Financial Technology (Digital Payment) In MSMEs - Ummasyroh, Ummasyroh; Astarina, Yesita; Riana, Dwi; Muharramah, Ulfah; Africano, Fernando (Asean International Journal of Business, 2024)
Purpose – This research aims to initiate digital transformation in MSMEs under the guidance of Rumah BUMN South Sumatra by implementing a digital payment system using QRIS. Methodology/approach – This research was carried out using a quantitative descriptive approach, which aims to see the application of fintech through digital payments as an effort to develop MSME businesses. The population in this study was 20 MSMEs assisted by Rumah BUMN South Sumatra, while the sampling technique used the census method, namely the entire population, was used as the research sample. The analysis method in this research uses path analysis with consumer interest as an intervening variable, data processing uses the help of the SEM PLS program 3.0. Findings – The results obtained that financial technology has a significant effect on consumer interest, financial technology has a significant effect on MSME business development, and consumer interest has a significant relationship with MSME business development with a positive correlation.